A Review of Euthanasia: Criminal and Medical Law Aspects in Indonesia - Iswanty, Muji (2018)
The development of science is a separate guide for health care workers to provide better health care and also the complex condition of patient, and even tend to be critical. The issue of euthanasia is a dilemma that places in a dilemmatic position. It is growing, but it is not compensated by legal certainty. The issue to be discussed in this paper is how the restrictions imposed by law for euthanasia action requires a review of medical science and criminal law as well as aspects of human rights. The results show that normatively, euthanasia has not been clearly regulated. For this reason, a doctor always remembers the obligation and responsibility to protect human beings, it means that any country of the world a doctor has an obligation to “respect every human life from the conception.” In this case it means that no matter how serious a patient, every doctor should still protect and sustain the life of patient. In terms of criminal law, euthanasia is a prohibited act in which the articles in the Indonesian Criminal Code relating to euthanasia. Social reasons as developed in society to legalize euthanasia is not true. By developments in society today, and it is possible for judges to issue decision on euthanasia based on the doctrine of law degree and the limitative-medical requirements. There is a justification for life disappearance but must be viewed casuistically and in a limitative nature. Keywords: Euthanasia; Human Rights; Criminal Law; Medical La